Edukasi Mengenai Penyakit Berbasis Lingkungan Sebagai Dampak Bencana Perubahan Iklim - Erian Fatria; Agus Priadi; Febrian Rahmat Suwandi SN; Fauzi Ashra; Savio Pipo Boytoleny; Sunarti Sunarti (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2024)
The background of the implementation of this community service is based on the many incidents of environment-based diseases that occur at every level of society as a result of the phenomenon of climate change. Education about environment-based diseases is a solution that can be offered in the context of anticipating climate change disaster adaptation and mitigation. The purpose of this community service is to provide information to the public regarding climate literacy and the importance of efforts to prevent and overcome various environmental-based disease events. The method in this community service is a quantitative method involving 39 Public Health students at Universitas Prima Nusantara Bukittinggi, who were selected by purposive sampling, after the education is carried out, the group will be given a test instrument to determine student knowledge about environment-based diseases and global climate change. The analysis technique used is a descriptive technique which is carried out to map the knowledge gained by students. The results of this community service are able to provide new knowledge to students related to the incidence of environment-based diseases as an impact of global climate change, by getting the most scores in the good predicate interval (71-85), reaching  46.15% of the total students. And it is concluded that the educational method on environment-based diseases is effective to be given in the context of adaptation and mitigation of climate change disasters. The findings obtained can be taken into consideration for the community on the importance of increasing knowledge in achieving a balance of human quality of life with environmental quality in the context of achieving the 3rd SDGs, namely guaranteed health and well-being and the 13th SDGs, namely climate action.